Abstrato ou concreto? As representações mentais da economia compartilhada - Sordi, Jefferson Dobner (2020)
The sharing economy, as a phenomenon of research and consumption, draws the attention of the institutions that dialogue with it. Companies, government, universities and society try to understand how platforms inserted in an economic model based on the sharing of goods and services, focused on access and not on property, attract the attention of individuals and, in many segments, are already the first option within of the set of evaluations in the decision-making process, see the case of Airbnb or Uber, for example. However, not all sectors show such an effective behavior in the shared economy. The literature has demonstrated the existence of a gap between attitude and behavior within this context. It was evidenced that there is a difference in the intensity of the relationship between the two constructs that does not occur in most cases. Based on this observation, the present thesis aimed to understand how this gap is still present and propose a cognitive explanation not yet worked on in the literature of shared economics: mental construals. Coming from Social Psychology, Construal Level Theory proposes that the evaluations of individuals about a given situation (or object) can be done at more abstract (and distant) and more concrete (and near) levels. The individual's answer is given by the psychological distance to the analyzed situation. The use of this theory to analyze the consumption practices of the sharing economy was developed based on three articles. In the first, a theoretical essay discussing how the dimensions of the shared economy and their respective mental constructions can affect the relationship between attitude and behavior in the studied context. The second paper, shows that the gap remains, and its intensity changes according to the nature of the business being evaluated.. Finally, the last article deepens the investigation of the gap, studying it in isolation. At the end of this last text, a framework is proposed evidencing predecessors, consequent, and in a special way, possible moderators of the gap between the constructs The results of the three combined articles leave as a contribution to the literature that the gap still persists and that mental constructions tend to decrease the intensity of the relationship between attitude and behavior, especially in business proposals that have the sharing and the common good as purposes.